1991
DOI: 10.1128/jcm.29.11.2609-2613.1991
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and serial propagation of a bovine group C rotavirus in a monkey kidney cell line (MA104)

Abstract: A virus (designated the Shintoku strain) which was morphologically indistinguishable from group A rotaviruses was detected in the feces of adult cows with diarrhea in Japan. The virus contained 11 segments of double-stranded RNA and had an electrophoretic migration pattern in polyacrylamide gels similar to that of other group C rotaviruses (4-3-2-2). Feces containing the bovine virus reacted with antiserum to porcine group C rotavirus (Cowden strain) but not group A or B rotaviruses in immunoelectron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
67
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 35 publications
0
67
0
Order By: Relevance
“…Group C rotavirus (GCRV) was first detected in pigs in 1980 (Saif et al, 1980) and has been subsequently identified in humans, ferrets, and cattle (Rodger et al, 1982;Torres-Median, 1987;Tsunemitsu et al, 1991). Since then, the global distribution of human GCRVs has been established; they are suspected of being an emerging pathogen Caul et al, 1990;Esona et al, 2008;Iizuka et al, 2006;Kuzuya et al, , 2007Medici et al, 2009;Steyer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Group C rotavirus (GCRV) was first detected in pigs in 1980 (Saif et al, 1980) and has been subsequently identified in humans, ferrets, and cattle (Rodger et al, 1982;Torres-Median, 1987;Tsunemitsu et al, 1991). Since then, the global distribution of human GCRVs has been established; they are suspected of being an emerging pathogen Caul et al, 1990;Esona et al, 2008;Iizuka et al, 2006;Kuzuya et al, , 2007Medici et al, 2009;Steyer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Jarasvech Chinsangaram et al in cattle [2][3][4][5][6]. Among these three groups, only group A bovine rotavirus has been studied extensively because most of the group A bovine rotaviruses are cultivable in cell culture [5].…”
mentioning
confidence: 99%
“…A few cases of group B bovine rotavirus have been reported in the U.S. [7][8][9][10]. Bovine group C rotavirus (shintoku strain) has been isolated from adult cows with diarrhea in Japan although the isolation of this virus in the U.S. has never been reported [6].…”
mentioning
confidence: 99%
“…Bovine coronavirus (BCV) is a primary cause of adult cattle diarrhea, including winter dysentery (WD), which is characterized by the sudden onset of epidemic diarrhea, which occasionally presents with bloody feces and reduced milk production during the winter season [15,32,36,44]. In addition, bovine group A rotavirus (GAR) [14,38], bovine group B rotavirus (GBR) [7,18,45], bovine group C rotavirus (GCR) [28,42], and bovine torovirus (BToV) [19,22] also have been identified in field cases of adult cattle diarrhea. However, the frequency of adult cattle diarrhea caused by these viruses remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine GAR is one of the major pathogens that causes acute diarrhea in neonatal calves worldwide [11] and is occasionally responsible for diarrhea in adult cattle [14,38]. Bovine GBR and GCR have been associated with epidemic outbreaks of diarrhea in adult cattle but are relatively uncommon in calves [7,18,28,42,45], and in several outbreaks, marked drops in milk production have been observed [18,28,42]. Rotaviruses can be genotyped using the outer capsid proteins VP7 and VP4 to define the G and P genotype, respectively, based on sequence differences of the respective genes [12].…”
Section: Introductionmentioning
confidence: 99%